Formalism versus pragmatism – A comparative legal and empirical analysis of the German and Dutch criminal justice systems with regard to effectiveness and efficiency. Issue 4 (August 2021) - Hofmann, Robin
The German and the Dutch criminal justice systems not only share a common legal history but also follow the inquisitorial tradition with the prosecution playing a strong role. Despite these commonalities, there are a number of remarkable differences between the two jurisdictions, particularly with a view to procedural law and legal practices. While the German criminal law is known for being formal and rather doctrinal, the Dutch system is strongly driven by pragmatism and efficiency. This efficiency has become an important factor for the progressing Europeanization of criminal law and increasingly influences German criminal procedural law. This article compares selected aspects of the Dutch and German criminal justice systems. While previous legal comparative studies of the two neighbouring countries have focused on substantive criminal law, this paper will mainly deal with procedural criminal law and prosecutorial practices. The emphasis will be on criminal justice effectiveness and efficiency. Some of the questions addressed are: what constitutes an efficient criminal justice system? How is efficiency defined and implemented in legal practice? A variety of indicators for criminal justice efficiency are proposed and applied to criminal proceedings, prosecutorial practices and the sentencing systems in both countries.